Four new species of Epacanthion Wieser, 1953 (Nematoda: Thoracostomopsidae) in intertidal sediments of the Nanji Islands from the East China Sea - Shi, Benze; Xu, Kuidong (Zootaxa, 2016)
Four new species of Epacanthion are described from intertidal sandy sediments in the Nanji Islands National Marine Natural Reserve from the East China Sea. Males of all four new species have short spicules (< 2 anal body diameter) and a characteristic cervical circle of distinctly short and densely arranged setae at the pharyngeal region: Epacanthion hirsutum sp. nov. with a cervical circle of a single row of setae posterior to the nerve ring; E. longicaudatum sp. nov. with a cervical circle of 16 bundles each composed of six setae in two longitudinal rows posterior to the nerve ring; E. fasciculatum sp. nov. with a cervical circle of 18 bundles each composed of about 10 setae posterior to the nerve ring; and E. sparsisetae sp. nov. with a cervical circle of eight bundles each composed of about 10 setae anterior to the nerve ring. Among the known species of Epacanthion, only two species possess these features: E. quadridisci and E. gorgonocephalum. Epacanthion quadridiscus has six bundles of setae situated at the same level of the nerve ring, while E. gorgonocephalum has distinctly dense setae forming a wide band at the pharyngeal region. Epacanthion hirsutum sp. nov. differs from all congeners by the cervical circle composed of a single row of setae. Epacanthion sparsisetae sp. nov. is unique in having the cervical circle of bundles anterior to the nerve ring. Epacanthion longicaudatum sp. nov. differs from E. fasciculatum sp. nov. by the body size and the structure of the cervical circle. An updated diagnostic key to 28 valid species of Epacanthion is proposed.